The effect of high temperatures (30 degrees Celsius) on biological nutrient removal performance - Mellin, Hannu Kaarlo Olavi (Department of Civil Engineering, 2016)
The main objective of this investigation was to evaluate activated sludge biological nutrient removal (BNR) performance at elevated temperatures for possible application of nitrification denitrification (ND) and ND biological excess phosphorus removal (NDBEPR) systems to municipal wastewater treatment in the equatorial and tropical regions or to combined treatment of municipal and anaerobically (thermophilic) pretreated paper and pulp industry wastewaters in the very cold northern forested regions. To accomplish this objective, a ND Modified Ludzack Ettinger (MLE) system and a NDBEPR University of Cape Town (UCT) system were operated at 30°C and 10 days sludge age for a period of 582 days. During the investigation 41 sewage batches, each lasting about two weeks, of real sewage from the Mitchells Plain municipal wastewater treatment plant (Western Cape, South Africa) were fed to the systems. The two systems were sampled and tested ,almost daily for Chemical Oxygen Demand (COD), Total Kjeldahl Nitrogen (TKN), Free and Saline Ammonia (FSA), nitrate, nitrite, Total Phosphorus, Volatile Settleable Solids (VSS), Total Settleable Solids (TSS), pH, Oxygen Utilization Rate (OUR) and diluted sludge volume index (DSVI) in the influent, anaerobic, anoxic and aerobic reactors and effluent as appropriate. Also, in order to determine the kinetic rates of nitrification, denitrification and readily biodegradable COD (RBCOD) conversion to Volatile Fatty Acids (VF A), aerobic, anoxic and anaerobic batch tests were conducted at 30°C on sludge harvested from the two systems and microscopic examination of the sludges was undertaken every four weeks to identify the filamentous organisms in the systems.